Is tattooing associated with increased seroprevalence of transfusion-transmitted infections among blood donors: A single-center study from Southeastern India - Charumathy Arjunan; Abhishekh Basavarajegowda (Asian Journal of Transfusion Science)
INTRODUCTION: The regulations in India mandate a blanket deferral period of 12 months for donors from the time of acquiring a tattoo. The rationale is that using nonsterile needles, the same dyes for many persons, and other unhygienic practices result in the transmission of blood-borne infections. However, currently, autoclavable tattoo equipment, professional tattoo gun, single-use dye, and needle for tattooing have come up and are known to be devoid of the risks mentioned above. Hence, this study was designed to assess if the seroprevalence of transfusion-transmitted infections (TTIs) among tattooed blood donors was higher than in other nontattooed donors. METHODOLOGY: This cross-sectional comparative study was conducted in the Department of Transfusion Medicine at the tertiary care teaching hospital in Pondicherry from September 2017 to May 2019. The study group included blood donors in the age group of 18–60 years with one or more tattoos, and the control group was chosen among blood donors of the same age without a tattoo. The sampling technique was consecutive. The serological prevalence of the two groups was compared for HIV, hepatitis B virus, hepatitis C virus, Syphilis, and Malaria. RESULTS: A total of 368 donors were recruited for the study, 184 donors with tattoos and 184 donors without a tattoo. The detected seroprevalence of TTI among the tattooed and nontattooed groups was 3.8% and 4.3%, respectively. There was no significant association found between tattooing and seroprevalence of TTI. About 60% of the ones who got a tattoo had obtained it from a licensed tattoo parlor. CONCLUSION: We found that the seroprevalence of TTI among tattooed donors was similar to that of nontattooed donors. However, the seroprevalence among donors who had undergone more than one tattooing experience was higher than those who had a single tattooing event.